Comparison of Traditional Games and Modern Games at State Elementary School 1 Guntung Manggis - Rossi Apriliani Dewi; Norma Anggara; Akhmad Amirudin (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to identify the comparison of traditional games and modern games against the skills of students at State Elementary School 1 Guntung Manggis. In today’s digital era, ,modern games are increasingly dominating than traditional games, so it is important to explore its effect on children’s skills. The type of research used is qualitative descriptive, with data collection through observation and interviews. The data analysis process is carried out through data collection, data reduction, data presentation, and conclusion drawing. The results of the study showed that traditional games such as gobak sodor, forts, clogs, hide and seek and hid plots were more often played at the State Elementary School 1 Guntung Manggis and had a significant impact on the social, physical, and emotional development of students. Meanwhile, while modern games such as rubik, monopoly, roblox, free fire and pubg are also popular, the negative impact is seen in the reduction of social interaction and the tendency to play individually. The conclusion is that games have a greater positive impact than modern games, Especially in the aspects of social interaction, cooperation, thinking skills, and emotional and behavioral management.